Removing Incentives for "Dumbing Down" Through Curriculum Re-structure and Additional Study Time - Stanley, Gordon; MacCann, Robert G. (Education Policy Analysis Archives, 2005)
Offering differentiated courses to cater for a wide range of ability can lead to"dumbing down" when brighter students choose easier courses, which they can handle well without undue effort. This occurred when differentiated English courses were introduced in the senior secondary certificate in the state of New South Wales (NSW) in Australia. To avoid this trend continuing, new differentiated courses reported on a common scale were developed. At the same time a new preparatory course was provided to support weaker students to achieve the minimal standard in English. The resulting reform has led to stronger outcomes in English and increasing numbers of students taking more demanding courses. Defining clear standards on a common scale has led to better achievement for all students without having an adverse effect on participation in the senior secondary certificate.